CRIMINALIZATION, FEMINISM, POPULAR DEMAND AND HUMAN RIGHTS. THE SPANISH CASE - Contreras Ugarte, Jesús Víctor Alfredo (2019)
In this work I seek to awake a reflection on the legal situation that is causing discrimination against men because of sex and that, in turn, benefits women granting them procedural and normative privileges, for the same reason. I do not deny the historical discrimination women have suffered over the time and in this article I give clear evidence of this and affirm that this discriminatory idea still remains alive in some heads, even in notorious persons of our society. However, in this article I reject that this situation can justify from the Law legal rules that harass the dignity of man for the simple fact of being. The State, wanting to give immediate and efficient answers, especially through the popular pressure of some interested people, has ended up establishing abusive and disproportionate norms against men. Being able to, unfairly mistreat a man in his dignity, because the law facilitates it, this is also violence.